Effects of Exercise Training in Postoperative Patients With Congenital Heart Disease: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials. Issue 5 (3rd March 2020) - Xu, Cheng; Su, Xiaoqi; Ma, Siyu; Shu, Yaqin; Zhang, Yuxi; Hu, Yuanli; Mo, Xuming
Abstract : Background: The purpose of this meta‐analysis is to assess the effects of exercise training on quality of life, specific biomarkers, exercise capacity, and vascular function in congenital heart disease (CHD) subjects after surgery. Methods and Results: We searched the Cochrane Central Register of Controlled Trials, MEDLINE, and EMBASE from the date of the inception of the database through April 2019. Altogether, 1161 records were identified in the literature search. Studies evaluating outcomes before and after exercise training among postoperative patients with congenital heart disease were included. The assessed outcomes were exercise capacity, vascular function, serum NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) levels and quality of life. We analyzed heterogeneity by using the I 2 statistic and evaluated the evidence quality according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) guidelines. Nine randomized controlled trials were included. The evidence indicated that exercise interventions increased the one of the quality of life questionnaire score (mean difference=3.19 [95% CI, 0.23, 6.16]; P =0.03; I 2 =39%) from the score before the interventions. However, no alterations in exercise capacity, vascular function, NT‐proBNP or quality of life were observed after exercise training. The results of the subgroup analysis showed that NT‐proBNP levels were lower in the group with exercise training than in the group without exercise training over the same duration of follow‐up. The evidence quality was generally assessed to be low. Conclusions: In conclusion, there is insufficient evidence to suggest that physical exercise improves long‐term follow‐up outcomes of congenital heart disease, although it has some minor effects on quality of life.